DEVELOPMENT OF SNAKES AND LADDERS EDUCATIONAL GAME AND STUDENTS’ LEARNING OUTCOMES ON THE PROBABILITY MATERIAL IN GRADE VIII OF SMP - windi veber yanti sembiring; Fibri Rakhmawati (Prima: Jurnal Pendidikan Matematika, 2026)
This study aims to develop and test the feasibility of the snakes and ladders educational game media on probability material for grade VIII junior high school. The background of this study departs from the results of interviews with teachers who showed that students still have difficulty understanding the concept of probability because learning tends to be conventional and less interactive. This study uses a 4D development model (Define, Design, Develop, and Disseminate). Data collection techniques include interviews, expert validation questionnaires, teacher and student response questionnaires, and learning outcome tests (pretest and posttest). The results showed that the snakes and ladders educational game media is valid for use in learning, with validation scores from media experts of 87.5% and material experts of 95.83%, both of which are in the very valid category. From the practical aspect, the media is considered very practical, with an average student response of 87% and a teacher response of 93.37%. The effectiveness of the media is shown through an increase in student learning outcomes with an average N-Gain score of 76.52% in the high category. Thus, the snakes and ladders educational game has proven valid, practical, and effective in enhancing understanding of the concept of probability and creating a fun, interactive, and meaningful learning environment. This medium is suitable for use as an innovative alternative in mathematics learning at the junior high school level.